Sustainable Capture Fisheries Management Strategy in Dumai City, Riau Province - Novindra, Novindra; Sapanli, Kastana; Rosanti, Novi; Ramadona, Tomi; Ferani, Lathifa Marsya Nathania (Policy Brief Pertanian, Kelautan, dan Biosains Tropika, 2024)
Dumai City is located in Riau Province which is an important economic and trade center for the community. However, due to the large number of industrial areas that exist around coastal areas, this has had an impact on the capture fisheries sector. This results in serious challenges in resource utilization and economic development. One of the challenges that needs to be solved is pollution around the coast which threatens the sustainability of capture fisheries resources on the coast of Dumai City. Therefore, the issue of coastal pollution and its impact on reducing fishermen's catches is a challenge in the economic management of sustainable capture fisheries in Dumai City.